Influence of nitrogen and phosphorus fertilizers on the productivity of groundnut (Bangladesh Journal of Agricultural Research, 2007)
Field experiments were conducted at the Bangabandhu Shiekh Mujibur Rahman Agricultural University (BSMRAU), Gazipur in 2000-2001 and 2001-2002 to study the effects of nitrogen and phosphorus fertilization on the number of pods per plant, 100-seed weight, pod yield per ha, shelling percentage, seed oil content, N and P use efficiency of groundnut. Four levels of nitrogen (0, 20, 40, and 60 kg N/ha), four levels of phosphorus (0, 13, 26, and 39 kg P/ha) and three varieties of groundnut (Dhaka-1, Zhingabadam, and Basantibadam) were the experimental materials. Application of nitrogen and phosphorus fertilizers exerted significant effects on all the parameters under study. The highest pod yield in Basantibadam was obtained with 60 kg N and 39 kg P/ha while 60 kg N and 26 kg P/ha gave the highest yield in Dhaka-1 and Zhingabadam. Dhaka-1 and Zhingabadam had more shelling percentage and oil content compared to Basantibadam. A decreasing trend in oil content was observed at higher doses of N and P application across the varieties. The N use efficiency increased upto 40 kg N/ha for both Zhingabadam and Basantibadam for Dhaka-1, while 20 kg N/ha for Dhaka-1 groundnut. The P use efficiency was found to be higher at 26 kg P/ha for Basantibadam and 13 kg P/ha for Dhaka-1 and Zhingabadam. Bangladesh J. Agril. Res. 32(2) 2007: 283-290.